Emotional role and place of lullabies and childhood songs in Republic of Benin.... - FIOSSI KPADONOU, EMILIE ABLAWA; SESSOU, Dagbé Viva; KPADONOU GODO, TOUSSAINT; AGOSSOU, THÉRÈSE ANTOINETTE. A. (My University, 2017)
An important channel of communication and induction of emotions and feelings remains music, in its lIarious characteristics and type of melody. Childhood sangs or lullabies are a specifie musical type. They immerse the subject in particular effeets, This study was carried out ta analyze in adolescents the effeets associated with lullabies and childhood sangs kept in memory. The study was cross-sectional with descriptive focus and covered 269 adolescents in formal or informai training in southern Benin. The sampling mode was convenient. The sUlVey lasted 2 months in 2011 and was based on observation and a self-questionnaire. The pracessing and analysis of the data was carried out in 1BM 5PSS Statistics, with a significance threshold of 5%. The recall, Iistening. or interpretation of the lullabies used ta soothe the baby he/she had been plunges the adolescent into the evocation of childhood memories and the remembrance of the parental affection received in the childhood (62.90/0). These teenagers hum lullabies in moments of family joy or in situations of solitude, despair, feelings of emotionallack or inattention, sadness, anger or anguish. The personal experience related to Iistening, humming or performing the lullabies used ta soothe the baby was influenced by gender, with p comprised between 0.034 and 0.04B. Lullabies can prave ta be a calming tool ta better explore for better use in child psychiatry.
Keywords: Keywords: Lullabies; childhood effect; adolescent; child psychiatry.